The Impact of Transformational Leadership on Employee Productivity, Happiness, and Burnout: The Mediating Role of Employee Engagement and Stress - ALI, AMNEH M. I. (2024)
Transformational leadership (TL) is critical in addressing challenges in today’s competitive and stressful organizational environments. This study examines the impact of TL on employee productivity (EP), happiness at work (HAW), and job burnout (JB) in Palestinian ministries. It also investigates the mediating roles of employee engagement (EE) and job stress (JS). The study used a quantitative cross-sectional survey of 535 low- and middle-ranking employees in Palestinian ministries. Structural equation modeling was applied to test the hypotheses. Findings revealed that TL positively influences EE, EP, and HAW, while negatively affecting JS and JB. EE positively impacts EP and HAW, while JS negatively impacts them and increases JB. Both EE and JS significantly mediate the relationships between TL and EP, HAW, and JB. The study offers practical insights for enhancing employee performance, engagement, and well-being while reducing stress and burnout in public institutions.